Paving the translational ageing research pathway—training the next generation of researchers. (6th November 2020) - Tullo, Ellen; Dodds, Richard M; Birkbeck, Matthew; Habiballa, Leena; Sayer, Avan Aihie
Abstract: Ageing is an archetypal translational research topic, spanning a breadth of academic disciplines. This poses challenges for researchers aiming to act upon laboratory findings to develop and implement interventions that directly benefit older people. Divisions between distinct academic research cultures present barriers to collaborative working. We present potential strategies to improve the translation of ageing research with examples of successful projects working across disciplines. Researchers and clinicians in ageing should be supported to develop a translational interest and receive specific training about translational research.